Foram dois, "Voltamos em cinco": família e reprodução assistida em Marechal Cândido Rondon - Heidemann, Samuelli Cristine Fernandes (2018)
This dissertation aims to evidence the assisted reproduction like a way of maintaining "traditional" relationships of the modern nuclear family, centered on love, on affection, on idea of the couple’s "plan", which connects parents to their children, and in blood and family name categories. The research, conducted in 2017 and 2018, in the small town of Marechal Cândido Rondon / PR, focused on the lived experience by eight women ando ne man who used technological reproductive methods such as the artificial insemination and in vitro fertilization. These methods operate aggressively in their bodies of these women by intensive use of medicalization, but does not question how the techniques are disclosed and marketed. As a methodological strategy, in addition to analytical and bibliographic references about the subject, the construction of data was done through unstructured interviews and other sources obtained on websites and social networks like the facebook. The argument is that, for these women and their families, the Assisted Reproduction "corrects" the infertility and yours stigmatizing effects and, above all, leads to the realization of the biogenetic parental project, reinforcing the family nucleus composed by father, mother and biological child.